PENGARUH BERBAGAI DOSIS CITRININ TERHADAP KERUSAKAN STRUKTUR HEPATOSIT MENCIT (Mus musculus) PADA TIGA ZONA LOBULUS HEPAR - Hastuti, Utami Sri (Jurnal Kedokteran Brawijaya, 2006)
Citrinin is a sort of mycotoxin which caused mycotoxicosis. Citrinin is produced by Penicillium citrinum mold that can contaminate sort of food especially damaged beans.  Citrinin is known as nephrotoxic as well as hepatotoxic mycotoxin and caused hepatocite structure damage. This research was done: 1) to know the effect of citrinin to hepatocite structure damage; 2) to know the effect of citrinin dose difference to the value of the hepatocyte structure damage; 3) to know the effect of citrinin to the value of hepatocyte structure damage on three zones of hepar lobulus. The samples of this research were male mice (Mus musculus) var. BALB-C  at the age of three months. The experiment group of  mice was orally administered with citrinin in three doses, i.e: dose-1: 1 mg/kg BW; dose-2: 1,75 mg/kg BW; dose-3: 2,5 mg/kg BW. Hepatocyte structure damage is observed on centrilobular zone, midzone, and perifer zone. The hepatocyte structure damage examination is done by histopathologycal andultra structural examination by electron microscope.